PENYULUHAN SUMBER DAYA MANUSIA UNTUK BUDAYA MODERN RETAIL PADA 100 OUTLET MODERN RETAIL TRADISIONAL UNTUK PENGEMBANGAN EKONOMI WILAYAH DI KOTA MAGELANG, JAWA TENGAH 2022-2023 - Iwan Satriyo Nugroho, Iwan Satriyo Nugroho; Darwin Nahwan, Darwin Nahwan; Muhajirin, Muhajirin; Abdussalam, Abdussalam; Dila Sekar Arum Sari , Dila Sekar Arum Sari; Reina marsela, Reina marsela (Media Nusantara, 2023)
Retail has an important role in the supply chain because it is the spearhead of the distribution channel which is in direct contact with consumers. Indonesian Retail Sales Growth was reported at 5.5% in September 2022. This record is an increase compared to the previous 4.9% for 2022-08. Indonesia Retail Sales Growth data is updated monthly, averaging 8.1 % from 2011-01 to 2022-09, with 141 observations. This data reached a high of 28.2 % in 2013-12 and a record low of -20.6 %. Magelang City is one of the largest tourist cities in Indonesia. The Magelang City tourism office projects that tourist visits in the city could reach around three million people by the end of 2022 or much higher than the target of 1.5 million tourists. In tourist destination-based cities, the role of retail is very important in meeting the needs of the community and migrant tourists. Consumer good companies try to design and build marketing strategies to advance their companies. Likewise, the role of PT. HM. Sampoerna Tbk under the international affiliate PT Phillip Morris Intenationa;l as a business citizen also takes an active role in encouraging an inclusive people's economy as a form of commitment to support equal distribution of economic progress throughout Indonesia. Carried out through the Sampoerna Retail Community (SRC) program, Sampoerna has been developing and increasing the competitiveness of traditional grocery stores since 2008 and has now built more than 120,000 grocery stores throughout Indonesia.